2015
DOI: 10.1159/000365703
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Demographic and Clinical Factors on Surgical Outcomes of the Transobturator Tape Procedure in Patients with Stress Urinary Incontinence

Abstract: Background: Stress urinary incontinence (SUI) is a prevalent problem within the female population with associated high psycho-social impact. Transobturator tape procedure is a well-established procedure to treat the same, but the results may be influenced by various preoperative demographic and clinical factors. Patients and Methods: The study group comprised of 50 female patients with genuine SUI, who were then divided into subgroups based on demographic and clinical factors. Outcomes were compared between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Stress urinary incontinence (SUI) is extensively accepted as a social problem and defined as the involuntary leakage of urine with effort ( 1 ). Generally, causes of incontinence are hypermobility due to the loss of urethral support and lower pressure transmission to the urethra, compared to the urinary bladder ( 2 ). In the last decade, mid-urethral sling surgery has become the standard procedure for treatment of SUI in women.…”
Section: Introductionmentioning
confidence: 99%
“…Stress urinary incontinence (SUI) is extensively accepted as a social problem and defined as the involuntary leakage of urine with effort ( 1 ). Generally, causes of incontinence are hypermobility due to the loss of urethral support and lower pressure transmission to the urethra, compared to the urinary bladder ( 2 ). In the last decade, mid-urethral sling surgery has become the standard procedure for treatment of SUI in women.…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal et al reported that TOT surgery was more successful in premenopausal patients, those younger than 50 years, and those with a urethral mobility of greater than 30 degrees. 21 In contrast, Yasa et al showed that TOT surgery yielded as successful outcomes for the elderly and postmenopausal patients as for young and premenopausal women. 22 Esin et al compared obese and non-obese groups and found no effect for obesity on the results of TOT surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Yasa et al showed that TOT surgery in SUI treatment had high rates of success and patient satisfaction and a low postoperative morbidity rate in postmenopausal women aged over 65 years ( 15 ). Agarwal et al reported that TOT surgery was more successful in premenopausal women younger than 50 years with a urethral mobility greater than 30 degrees ( 16 ). In the present study, there was no difference between the postmenopausal and premenopausal groups in terms of TOT success and fifth-year follow-up evaluations.…”
Section: Discussionmentioning
confidence: 99%